Designing e-Local Content of Teaching Materials for Extensive Reading Course: Lecturer’s Voice - Vebrianti Umar (The Study Program of English Education of Palangka Raya University, 2022)
This research focus on designing e-local content of teaching materials for extensive reading course: Lecturer’s voice. It applied R&D based on ADDIE MODEL. ADDIE means Analysis, Design, Development, Implementation and Evaluation. Furthermore, Interview and questionnaire as the instrument of collecting data. The result of this research revealed that the lecturers interested to use this reading material for teaching extensive reading course. It is proved by the positive response given by the lecturer. From 19 distributed questions, 18 questions has Yes response (1). The percentage of the score 1 is 100%, and it categorized as excellent. Moreover, 1 question has No (0)response, and the category of score 0 is poor. Refers to the gathered score, the E-Local Content of teaching materials is feasible to use as the appropriate reading materials for teaching extensive reading course based on lecturer’s voice.